2017
DOI: 10.1177/1748301817729953
|View full text |Cite
|
Sign up to set email alerts
|

Traffic fatalities prediction using support vector machine with hybrid particle swarm optimization

Abstract: Road traffic safety is essential, therefore in order to predict traffic fatalities effectively and promote the harmonious development of transportation, a traffic fatalities prediction model based on support vector machine is established in this paper. The selection of parameters greatly affects the prediction accuracy of support vector machine. Introducing particle swarm optimization can find the optimal parameters and improve the prediction accuracy of support vector machine by parameter optimization. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…In this study, the ANN model compared with the proposed Hybrid model. The Comparative performance of both models showed that the proposed model (Hybrid K means and random forest) performed better than the ANN model in terms of Precision, Recall, F1 score, Gu et al [21] PSO-SVM China -Xiao et al [52] SVM, KNN (Ensemble) I-880 data set 99.33% Castro et al [15] BN, JR8 and MLP DVSA-UK 72.39%, 72.02%, 71.70% Respectively Al-Radaideh et al [4] RF, ANN (backpropagation), SVM Uk 80.6%, 61.4%, 54.8% respectively Casado et al [14] LCC, MNL Spain -Wahab et al [51] MLP. SimpleCart, PART Ghana 72.16%, 73.45%, 73.81% respectively Sameen et al [40] MLP, BLR, RNN Malaysia 65.48%, 58.30%, 71.77% respectively Fentahun [18] J48, ID3, PART Ethiopia 81.21%, 81.01%, 81.18% Seid et al [42] HMR Ethiopia NA Abebe et al [1] DSA Ethiopia -Lytin et al [30] UBA Ethiopia - and Accuracy.…”
Section: Comparative Of Neural Network and Proposed Modelsmentioning
confidence: 95%
“…In this study, the ANN model compared with the proposed Hybrid model. The Comparative performance of both models showed that the proposed model (Hybrid K means and random forest) performed better than the ANN model in terms of Precision, Recall, F1 score, Gu et al [21] PSO-SVM China -Xiao et al [52] SVM, KNN (Ensemble) I-880 data set 99.33% Castro et al [15] BN, JR8 and MLP DVSA-UK 72.39%, 72.02%, 71.70% Respectively Al-Radaideh et al [4] RF, ANN (backpropagation), SVM Uk 80.6%, 61.4%, 54.8% respectively Casado et al [14] LCC, MNL Spain -Wahab et al [51] MLP. SimpleCart, PART Ghana 72.16%, 73.45%, 73.81% respectively Sameen et al [40] MLP, BLR, RNN Malaysia 65.48%, 58.30%, 71.77% respectively Fentahun [18] J48, ID3, PART Ethiopia 81.21%, 81.01%, 81.18% Seid et al [42] HMR Ethiopia NA Abebe et al [1] DSA Ethiopia -Lytin et al [30] UBA Ethiopia - and Accuracy.…”
Section: Comparative Of Neural Network and Proposed Modelsmentioning
confidence: 95%
“…Numerous impediments related to the statistical analysis of crash data remain [46]: the need to satisfy some statistical hypotheses [47] or the difficulty in managing several variables with many categories [48,49]. To overcome the deficiencies of these methods, road safety researchers have proposed new Non-Parametric Models [50], such as the Classification and Regression Tree (CART), widely used for the analysis of crash outcomes [51][52][53][54], and the Support Vector Machine (SVM) models which are normally utilized for the classification of crash injury severity [55][56][57][58][59]. Recently, Artificial Neural Network (ANN) has also been used to carry out the classification of crash severity and their applications have grown extraordinarily [60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%
“…6,13,14 Researchers also found the better prediction performance of the support vector machine (SVM) in developing crash injury severity models compared to other parametric models. [15][16][17] Moreover, despite limited application in transportation sector, multivariate adaptive regression splines technique has outstanding predictive power in crash injury analysis. [18][19] DL has recently become the new focus in transportation safety analysis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Random Forest Model is a promising data mining approach employed in many studies to prioritize the variables associated with crashes 6,13,14 . Researchers also found the better prediction performance of the support vector machine (SVM) in developing crash injury severity models compared to other parametric models 15–17 . Moreover, despite limited application in transportation sector, multivariate adaptive regression splines technique has outstanding predictive power in crash injury analysis 18–19 …”
Section: Introductionmentioning
confidence: 99%